Spatiotemporal patterns of atmospheric carbon monoxide over the Crimean Peninsula and the Black Sea: Sentinel-5Р/TROPOMI data (2019―2024) - Boychenko, S.G.; Khlobystov, D.I.; Maidanovych, N.M. (Geofizicheskiy Zhurnal, 2025)
The spatiotemporal distribution of the annual average of atmospheric CO column densities based on TROPOMI data from the Sentinel-5P satellite over the Crimean Peninsula and the Black Sea for 2019—2024 was analyzed. The average annual value over the Crimean Peninsula was (3.2―3.6)∙10–2 mol/m2, while over the surface of the Black Sea, it was (3.0―3.7)∙10‒2 mol/m2, and in coastal seawater — (3.7―4.2)∙10‒2 mol/m2. Spatial differences in the CO concentration may be associated with the characteristics of atmospheric processes (photochemical processes and atmospheric circulation), microbial oxidation, gas hydrate processes in the sea, and anthropogenic activity.